Faktor-Faktor yang Memengaruhi Kecemasan Keuangan pada Remaja Kota Surabaya - Jehan Sekarkinasih (Jurnal Ilmu Manajemen, 2021)
This study is the first study in Indonesia that examines the factors that influence financial anxiety. Financial anxiety is a negative psychological impact where there is a decrease in various aspects so that, in total, it causes stress levels to jump. This study focuses on adolescents who live in Surabaya, which, based on BPS data, the city of Surabaya has the largest population in East Java and is dominated by adolescents. This study aims to determine the effect of income, debt, financial knowledge, and financial satisfaction on financial anxiety. Data were collected by distributing online questionnaires with random sampling methods to 154 respondents. Then, data were tabulated in excel, analyzed and processed using multiple linear regression in SPSS. The result of this study indicates that none of the independent variables affects financial anxiety. This is presumably due to the lack of public knowledge about financial anxiety, especially among Surabaya adolescents. Few studies examine financial anxiety as the dependent variable, which thought to cause limited public knowledge about this topic. Therefore, this study is expected to increase knowledge, literacy, and public awareness regarding financial anxiety, especially to adolescents in Surabaya.